DAMPAK PANDEMI CORONA VIRUS TERHADAP PETANI MELON DI DESA PINGGIRSARI KECAMATAN NGANTRU - Kholiq, Agus; Fadillah, Muhamad (Universitas Ratu Samban, 2024)
This study aims to determine the impact of the Covid 19 pandemic on modern melon farmers during the month of Ramadan. This research was conducted on one of the Modern Melon Farmers in Pinggirsari Village, Ngantru District, Tulungagung Regency. This data collection and research was carried out for 2 months, from May 2020 to June 2020. The selection of research locations was carried out intentionally with the consideration that the farmer used modern agricultural methods (green house) on his own land area of 14 m x 40 m with a plant capacity of 1000 (one thousand) sticks. The results of this study indicate that modern melon farming can increase economic yields that are more optimal than Vegetable and Palawija crops. The benchmark of this research is that the economy of Modern Melon farmers is not affected in the local market during the Covid 19 pandemic. The marketing strategy carried out by modern melon farmers is still not optimal but has been directed with the methods of Consumer Segmentation Selection, Targeting, production continuity and positioning. So the human resources of modern farmers in Pinggirsari Village are classified as very ready and able to compete in the world of modern agriculture, because the agricultural factors of Pinggirsari Village have fulfilled the requirements with the diversity of variations in agricultural products, variations in price segments and promotion stages that are done well.